The The Effect of Giving Liquid Organic Fertilizer Made from Cow Urine Enriched by Agricultural Symbiotic Microbes on the Production of Taiwan Grass (Pennisetum purpureum Cv. Mott) - Mudhita, Ida Ketut; Saprudin; Mulyadi, Dedi; Nurlatipah, Siti (Universitas Veteran Bangun Nusantara, 2023)
This research aims to determine the effect of adding liquid organic fertilizer (POC) made from cow urine and agricultural symbiotic microbes on the growth and production of Taiwan grass (Pennisetum purpureum Cv. Mott). The research location is Natai Raya Village, Kumai District, West Kotawaringin Regency. The research method used a unidirectional Randomized Block Design (RAK) with 3 fertilizer treatments applied to Taiwanese grass with 6 replication plots. Treatment consists of: P1 using chemical fertilizer (PK) 100% NPK 200 kg/ha (40 g/plant) or P2 using PK 100%+25% POC (100 ml/plant), and P3 using PK 100%+50 % POC (200 ml/plant). The parameters observed were: plant height, stem diameter, number of tillers, leaf length, fresh weight production (BS), dry matter production (DW) and organic matter production (BO). The results of the study showed that there was a significant increase (P<0.05) with the addition of POC on the growth and production of Taiwan grass. Plant height increased significantly, the highest at P3 was 91.6 cm, an increase of 32.2% compared to P1 of 69.3 cm, at P2 it increased by 16.1%. The largest stem diameter in P3 was 2.18 cm, an increase of 29.9% compared to P1 of 1.68 cm, P2 increased 13.7%. The highest number of offspring at P3 18.56 increased 45.5% compared to P1 12.75, P2 increased 24.9%. The length of the longest leaf on P3 was 77.46 cm, an increase of 40.5% compared to P1 of 55.13 cm, P2 increased 34.55%. The highest BS production was at P3 28,550 tons/ha, an increase of 22.37% compared to P1 23.33 tons/ha, P2 increased 9.74%. BK production was highest at P3 13.38 tonnes/ha, an increase of 25.6% compared to P1 10.62 tonnes/ha, P2 increased 12.5%. The highest BO production was at P3 7,208 tonnes/ha, an increase of 30.62% compared to P1 5.51 tonnes/ha, P2 increased 15.92%. The conclusion of this research is that the higher the dose of liquid organic fertilizer made from cow urine, the higher the growth and production of Taiwanese grass. The optimal fertilizer dose is 100% chemical fertilizer treatment with added liquid organic fertilizer made from 50% cow urine. Keywords : Chemical fertilizer; liquid organic fertilizer; cow urine; agricultural symbiotic microbes; growth and production; Taiwan grass